Sexual aggressions in college students: the role of alcohol and rape myths - Romero-Sánchez, Mónica (Editorial Bonaventuriana, 2018)
In this paper we attempt to show the most significant aspects in the literature on sexual assaults in college students. Specifically, this review focuses on the role of alcohol and the myths or beliefs about rape, as some of these factors produce great negative impact on victims, decreasing their motivation to report incidents, and increasing self-blaming. The work is organized in three sections: a) reviewing the problem, b) the role of alcohol in the occurrence of sexual violence, and c) the influence of erroneous beliefs and myths built around the rape. Finally, some reflections are made on the efforts that must be done by research, to get a better understanding of the occurrence of sexual assaults on university population, in order to develop prevention and intervention programs more effective.